The relationship between reading comprehension and the complex structures of English nominalizations - Taup, Clarita Abella 1945- (1974)
The theory that the reader needs to recover the underlying deep structure in order to comprehend a sentence was tested in this study. This paper determined whether or not the skill of understanding underlying relationships of complex structures that result from transformations of basic sentence patterns is characteristic of efficient readers.
Thesis (M.Ed.)--University of the Philippines
Keywords: Reading